ENGLISH LEARNING STRATEGIES FOR EFL STUDENTS: INTERACTIVE AND EFFECTIVE APPROACHES TO ENHANCING LANGUAGE SKILLS - Triyogo, Agus; Hamdan (Lingustic, Literature and English Education, 2024)
Effective English language learning for EFL (English as a Foreign Language) students involves integrating communicative methodologies, technological resources, and cultural awareness. This paper explores various approaches such as Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT), emphasizing their roles in fostering communicative competence and language proficiency. CLT promotes interactive learning through real-life communication activities like debates and role-plays, enhancing fluency and pragmatic skills. TBLT complements CLT by engaging students in tasks that simulate authentic language use, promoting autonomy and problem-solving abilities. Technology plays a crucial role in modern EFL education, offering interactive tools and multimedia resources that cater to diverse learning styles and facilitate self-paced learning outside traditional classroom settings. Additionally, cultural competence is essential for effective communication, enabling students to navigate cross-cultural interactions with sensitivity and proficiency. By synthesizing these approaches and resources, educators create dynamic learning environments that prepare EFL students to communicate effectively in global contexts. This holistic approach not only supports language acquisition but also cultivates skills necessary for academic success and professional advancement in an interconnected world.